(8Z, 13Z, 18R, 20Z)-Strobilin and (7Z, 13Z, 18R, 20Z)-Felixinin : New bioactive furanosesterterpene tetronic acids from marine sponges of the Genus Ircinia (1997)
ABSTRACT: Methanolic extracts of the marine sponges Ircinia felix, I. strobilina and I. campana occurring in the Colombian Caribbean afforded similar complex mixtures of antimicrobial furanosesterterpene tetronic acids. Each mixture was acetylated and then fractionated by HPLC. GC, GC-MS and NMR analyses of the HPLC fractions revealed the novel (8Z,13Z,20Z)-strobilinin and (7Z,13Z,20Z)- felixinin, together with the know (8E,13Z,20Z)-strobilinin, (7E,13Z,20Z)-felixinin and (7E,12E,18R,20Z)-variabilin.